Analysis Of Critical Mixing Regions To Promote Biopolymer Synthesis In Fed-Batch Cultures Of Wautersia Eutropha - PRATAP R. PATNAIK (International Journal of Pharma and Bio Sciences, 2011)
Despite its advantages over synthetic polymers from petroleum-based feed-stocks, microbially produced poly-b-hydroxybutyrate (PHB) is not commercially competitive owing to low productivities. Productivity enhancement has been explored here through in silico experiments with Wautersia eutropha in fed-batch fermentations utilizing fructose as the carbon substrate and urea to provide nitrogen. The simulations were based on an experimentally validated kinetic model inserted into mass conservation equations for a bioreactor model that mimicked mixing through an interacting array of three well-mixed tanks. Performance data showed that cell growth and PHB formation were weakly dependent on local mixing in the region of the feed inlets and were determined largely by macromixing in the bulk fluid. However, the best performance depended on an optimum combination of mixing in the three regions, suggest that distributed mixing is an important factor. These results have a physical basis in the metabolism of PHB formation.